Titanium silicalite molecular sieve TS-1 and synthesis method thereof

By directly synthesizing titanium silicon molecular sieve TS-1 with a multi-stage pore structure with the assistance of high-active crystal embryo solution, the titanium silicon molecular sieve TS-1 is solved, and the synthesis of titanium silicon molecular sieve is high cost, complex operation and unfriendly to the environment is achieved, and a low-cost and high-efficiency multi-stage pore structure synthesis is achieved.

CN119841327AActive Publication Date: 2025-04-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311348410.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

The multi-stage pore structure synthesis method of titanium silicon molecular sieve TS-1 is costly, complex in operation and unenvironmentally unfriendly.

Method used

Grade pore TS-1 molecular sieve with micropore, mesoporous and macropore multiple structures assisted by high-activity embryo solution, using only a small amount of micropore template agents. The method includes mixing the raw materials containing silicon source, quaternary ammonium alkali template agent and water to obtain initial gel mixture A, and heating and crystallization under closed conditions, and then mixing the raw materials containing silicon source, alkali source, water, titanium source and protective agent to obtain gel mixture II, and finally mixing the two and heating and crystallization to obtain titanium silicon molecular sieve TS-1.

Benefits of technology

It realizes the synthesis of titanium silicon molecular sieve with multi-stage pore structure under low cost and simplified operating conditions, reducing production energy consumption, improving production efficiency, and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841327A_ABST
    Figure CN119841327A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium silicalite molecular sieve TS-1 and a synthesis method thereof. Comprising the following steps: mixing a silicon-containing source, a quaternary ammonium base template agent and water to obtain a mixture A, crystallizing I to obtain a crystal blank solution I, and enabling a solid of the crystal blank solution I to have an amorphous structure; mixing a silicon-containing source, an alkali source R, water, a titanium source and a protective agent S to obtain a mixture II; and mixing the crystal blank solution I and the mixture II to obtain a mixture III, and crystallizing the mixture II to obtain the titanium silicalite molecular sieve TS-1. According to the method disclosed by the invention, only a small amount of microporous template agent is used in the process of synthesizing the silicon-based crystal embryo solution, a mesoporous or macroporous pore-forming agent does not need to be added, and the dosage of the microporous template agent is only 1 / 10-1 / 20 of that of a conventional method, so that the problems of high molecular sieve cost, environmental pollution and the like caused by high price and high toxicity of a micromolecular microporous organic template agent and a mesoporous / macroporous pore-forming agent are solved; meanwhile, the content of framework Ti in the product is high, and non-framework Ti and TiO2 species are not contained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieves, and in particular relates to a titanium silicon molecular sieve TS-1 and a synthesis method thereof. Background Art

[0002] Since its first synthesis in 1983, titanium silicalite (TS-1) has been widely used in the preparation of fine chemicals due to its excellent catalytic performance in clean reaction systems with hydrogen peroxide as an oxidant (such as olefin epoxidation, phenol hydroxylation, etc.). However, the synthesis cost of TS-1 zeolite has always been high due to the limitation of synthetic raw materials, which limits its large-scale application. On the other hand, the smaller pore size in traditional TS-1 zeolite also limits its catalytic conversion of large molecular reactants.

[0003] The main reason for the high cost of TS-1 zeolite synthesis is that a large amount of expensive organic template agent tetrapropylammonium hydroxide (TPAOH), organic silicon source tetraethyl orthosilicate (TEOS) and organic titanium source tetrabutyl titanate (TBOT) are required in the synthesis process.

[0004] On the other hand, the prior art discloses a method of introducing mesoporous or macroporous pore formers into the TS-1 zeolite synthesis system to synthesize a multi-level pore TS-1 molecular sieve. However, these mesoporous pore formers usually have a complex structure and high cost, and some of them require a complicated synthesis process to obtain. Moreover, these mesoporous pore formers usually need to be calcined and removed when the molecular sieve is used, which also causes pollution to the environment. Summary of the invention

[0005] In view of this, the present invention provides a titanium silicate molecular sieve TS-1 and a synthesis method thereof, the main purpose of which is to solve the technical problems of high cost, complex operation and environmental unfriendliness in the synthesis method of the multi-level pore structure of titanium silicate molecular sieve TS-1.

[0006] In one aspect, the present invention provides a method for synthesizing titanium silicate molecular sieve TS-1, the method comprising the following steps:

[0007] S1: mixing raw materials containing a silicon source, a quaternary ammonium base template and water to obtain an initial gel mixture A, and heating and crystallizing the initial gel mixture A under a closed condition to obtain a crystal blank solution I; the solid in the crystal blank solution I has an amorphous structure;

[0008] S2: Mixing raw materials containing silicon source, alkali source R, water, titanium source and protective agent S to obtain gel mixture II;

[0009] S3: The crystal blank solution I in step S1 and the gel mixture II in step S2 are mixed to obtain a gel mixture III. The gel mixture III is heated and crystallized under closed conditions to obtain the titanium silicon molecular sieve TS-1.

[0010] The present invention provides a method for synthesizing a hierarchical pore TS-1 molecular sieve with a nano-aggregated morphology. The method can directly synthesize a hierarchical pore TS-1 molecular sieve with a multiple structure of micropores, mesopores and macropores with the assistance of a high-activity embryo solution containing embryo particles with an ultra-large specific surface area, using only a small amount of microporous template.

[0011] Optionally, in step S1, the solid particles in the crystal blank solution I have a size of 10 to 20 nm, and the particle structure contains a five-membered ring structure.

[0012] Optionally, in step S1, the molar ratio of the silicon source, the quaternary ammonium base template and the water in the initial gel mixture A is:

[0013] Template: SiO2 = 0.10-0.50:1;

[0014] H2O:SiO2=4~20:1;

[0015] The molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the template is calculated as the molar number of the quaternary ammonium base, and the molar number of the water is calculated as the molar number of H2O.

[0016] Optionally, in step S1, the molar ratio of the silicon source, the quaternary ammonium base template and the water in the initial gel mixture A is:

[0017] Template: SiO2 = 0.10-0.50:1; preferably 0.15-0.45:1, further preferably 0.20-0.40:1, further preferably 0.28-0.5:1, further preferably 0.3-0.5:1, further preferably 0.32-0.5:1, further preferably 0.35-0.5:1;

[0018] H2O:SiO2=4~20:1; preferably 6~18; further preferably 4~15:1, further preferably 4~14:1, further preferably 6~14:1, further preferably 4~12:1, further preferably 6~12:1.

[0019] Optionally, in step S1, the molar ratio of template: SiO2 in the initial gel mixture A is selected from any value among 0.10, 0.15, 0.20, 0.25, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.40, 0.45, 0.50 or any range between two thereof.

[0020] Optionally, in step S1, the molar ratio of H2O:SiO2 in the initial gel mixture A is selected from any value of 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range between any two of them.

[0021] Optionally, in step S2, the molar ratio of the silicon source, the titanium source, the alkali source R, the protective agent S and the water in the gel mixture II is:

[0022] SiO2: TiO2: R: S: H2O=1: (0.02~0.10): (0.01~0.20): (0.04~

[0023] 0.2): (6-30);

[0024] Among them, the molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of R is calculated as the molar number of the alkali source R, the S is calculated as the molar number of the protective agent S, and the water is calculated as the molar number of H2O.

[0025] Optionally, in the gel mixture II, TiO2:SiO2=0.02-0.05;

[0026] In the gel mixture II, R:SiO2=0.02-0.15;

[0027] In the gel mixture II, H2O:SiO2=12-20;

[0028] In the gel mixture II, S:TiO2=6-18;

[0029] Optionally, the gel mixture II in step S2 is obtained by mixing the initial gel mixture B and the initial gel mixture C;

[0030] The initial gel mixture B is obtained by mixing a silicon source, an alkali source R and water; the molar ratio of each component in the initial gel mixture B is:

[0031] R: SiO2 = 0-0.10:1, preferably 0.02-0.15;

[0032] H2O:SiO2=6-30:1, preferably 12-20;

[0033] The initial gel mixture C is obtained by mixing a titanium source and a protective agent S; the molar ratio of each component in the initial gel mixture C is:

[0034] S: TiO2 = 4-20:1, preferably 6-18;

[0035] Among them, the molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of the alkali source R is calculated as the molar number of R, the protective agent S is calculated as the molar number of S, and the water is calculated as the molar number of H2O.

[0036] Optionally, in the initial gel mixture B, the molar ratio of R:SiO2 is selected from any value among 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10 or any range between two values;

[0037] In the initial gel mixture B, the molar ratio of H2O:SiO2 is selected from any value among 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 or any range between two thereof.

[0038] Optionally, in the initial gel mixture C, the molar ratio of S:TiO2 is selected from any value among 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any range between two thereof.

[0039] Optionally, the structural formula of the quaternary ammonium base template is Formula I:

[0040]

[0041] Among them, R in Formula I 1 , R 2 , R 3 , R 4 Each independently selected from any one of C1 to C4 alkyl groups, R 1 , R 2 , R 3 and R 4 Same or different.

[0042] Optionally, the quaternary ammonium base template is selected from tetrapropylammonium hydroxide (TPAOH).

[0043] Optionally, in step S2, the initial gel mixture C is added dropwise to the initial gel mixture B under stirring to obtain the gel mixture II.

[0044] Optionally, in step S3, the product after heating and crystallization II is separated, washed and dried to obtain nano-sheet-shaped hierarchical pore TS-1 molecular sieve.

[0045] Optionally, in step S3, the molar content of SiO2 in the crystal blank solution I is 3-10% of the molar content of SiO2 in the gel mixture II.

[0046] Optionally, in step S3, the molar content of SiO2 in the crystal blank solution I is the molar content of SiO2 in the gel mixture II, selected from any value of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range between any two of them.

[0047] Optionally, in step S1, crystallization I is dynamic crystallization.

[0048] Optionally, in step S1, the temperature of crystallization I is 60-140°C, and the time of crystallization I is 0.5-24h; preferably 80-120°C, 2-16h; further preferably, the crystallization temperature is 60-120°C, and the crystallization time is 8-24h; further preferably, the crystallization temperature is 60-115°C, and the crystallization time is 9-24h.

[0049] Optionally, in step S1, the temperature of the crystallization I is selected from any value of 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, or any range between two thereof, and the time of the crystallization I is selected from any value of 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24h, or any range between two thereof.

[0050] Optionally, in step S3, the temperature of the crystallization II is 140-220°C, and the time of the crystallization II is 0.5-48 hours, preferably 160-220, 1-12 hours.

[0051] Optionally, in step S3, the temperature of the crystallization II is selected from any value of 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, or any range between two of them.

[0052] Optionally, the silicon source in the initial gel mixture A is selected from at least one of silica sol, methyl orthosilicate and ethyl orthosilicate.

[0053] Optionally, the silicon source in the gel mixture II is selected from at least one of silica sol, silica gel, chromatography column silica gel, methyl orthosilicate, ethyl orthosilicate and white carbon black.

[0054] Optionally, the titanium source is selected from at least one of tetraethyl titanate, tetrabutyl titanate, titanium tetrachloride, titanium sulfate and titanium isopropoxide.

[0055] Optionally, the protective agent S is selected from at least one of ethanol, isopropanol, acetylacetone, acetic acid and triethanolamine.

[0056] Optionally, the alkaline source R in the gel mixture II is selected from a compound having a structure of formula II:

[0057]

[0058] Wherein, R1, R2, and R3 in Formula II are independently selected from H or an alkyl group having 1 to 4 carbon atoms.

[0059] Optionally, the alkali source R is selected from at least one of ammonia water, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine and tri-n-butylamine.

[0060] Optionally, in step S1, the solid in the crystal blank solution I has a non-crystalline structure, and its XRD shows that it is amorphous, the particle size is 10 to 20 nm, and the particle structure contains a five-membered ring structure.

[0061] Optionally, in step S3, the titanium silicon molecular sieve TS-1 is calcined in air at a temperature of 400 to 600°C.

[0062] Optionally, in step S3, the calcination temperature is selected from any value of 400°C, 420°C, 450°C, 470°C, 190°C, 500°C, 520°C, 550°C, 580°C, 600°C or any range between two of them.

[0063] In a second aspect, the present invention provides a titanium silicalite molecular sieve TS-1, which is synthesized by the above-mentioned synthesis method.

[0064] Optionally, the titanium silicalite molecular sieve TS-1 has a multi-level pore structure of micropores and mesopores.

[0065] Optionally, the pore size of the mesopore is 5 nm to 50 nm, and the volume of the mesopore is 0.25 to 0.43 cm 3 g -1 .

[0066] Optionally, the pore size of the mesopore is 10 nm to 40 nm.

[0067] Optionally, the pore size of the mesopore is 20 nm to 30 nm.

[0068] Optionally, the titanium silicalite molecular sieve TS-1 has an MFI topological structure, wherein the Ti species has a four-coordinate structure.

[0069] Optionally, the pore size of the mesopore is 5 nm to 50 nm, and the volume of the mesopore is 0.25 to 0.43 cm 3 g -1 .

[0070] Optionally, the titanium silicalite molecular sieve TS-1 has a nano-flake morphology, and its length, width and thickness are 200-300 nm, 150-250 nm and 40-60 nm respectively.

[0071] In the present application, the "silicon-titanium ratio" refers to the molar ratio of silicon element to titanium element.

[0072] Compared with the prior art, the present invention has the following beneficial effects:

[0073] (1) The synthesis method provided by the present invention is assisted by a high-activity embryo solution, does not introduce a mesoporous or macroporous template, and only uses a small amount of a microporous template (only 1 / 10 to 1 / 20 of the template in the conventional method) to synthesize a titanium silicalite with a multi-pore structure of micropores, mesopores and macropores.

[0074] (2) The product obtained by the synthesis method provided by the present invention has a single Ti coordination and a high framework Ti content, and the product yield is as high as about 92%.

[0075] (3) The method provided by the present invention does not use a mesoporous template agent or complicated post-processing process in the entire process, and the synthesis cost is lower, the crystallization time is greatly shortened, the production efficiency is improved, and the production energy consumption is reduced; it is conducive to the large-scale production of titanium silicon molecular sieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 The X-ray diffraction pattern of embryo powder 1# provided in Example 1 of the present invention;

[0077] Figure 2 The infrared spectrum of the embryo powder 1# provided in Example 1 of the present invention;

[0078] Figure 3 The X-ray diffraction pattern of sample 1# provided in Example 1 of the present invention;

[0079] Figure 4 This is a transmission electron microscope image of sample 1# provided in Example 1 of the present invention;

[0080] Figure 5 The ultraviolet diffuse reflectance spectrum of sample 1# provided in Example 1 of the present invention;

[0081] Figure 6 The physical adsorption spectrum of sample 1# provided in Example 1 of the present invention;

[0082] Figure 7 A pore size distribution diagram of sample 1# provided in Example 1 of the present invention;

[0083] Figure 8 The X-ray diffraction pattern of the embryo powder comparison sample 1# provided in Comparative Example 1 of the present invention;

[0084] Fig. 9 This is the ultraviolet diffuse reflectance spectrum of comparative sample 1# provided in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0085] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0086] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment. The instruments and equipment used adopted the schemes and parameters recommended by the manufacturers.

[0087] The analysis method in the examples of this application is as follows:

[0088] X-ray powder diffraction phase analysis (XRD) was performed using an X'Pert PRO X-ray diffractometer from PANalytical of the Netherlands, with a Cu target, a Kα radiation source (λ=0.15418 nm), a voltage of 40 KV, and a current of 40 mA.

[0089] The elemental composition was determined using a Philips Magix 2424 X-ray fluorescence analyzer (XRF).

[0090] Low-temperature nitrogen physical adsorption was used to characterize the pore structure of the sample. The instrument used was ASAP2020 physical adsorption instrument from Micromeritics. The BET formula was used to calculate the specific surface area, and the BJH formula was used to calculate the pore distribution.

[0091] The yield of the sample was calculated according to the following formula:

[0092] Yield = (mass of the sample after calcination) ÷ (mass of SiO2 in mixture III + mass of TiO2) × 100%.

[0093] Example 1 Sample 1 # Synthesis

[0094] A mixed solution with a homogeneous molar ratio of 1SiO2:0.3TPAOH:15H2O was prepared using silica sol as a silicon source and tetrapropylammonium hydroxide as a microporous template, and then placed in a synthesis reactor with a polytetrafluoroethylene liner and crystallized at 100°C for 6 hours to obtain a homogeneous embryo solution I. A portion of the embryo solution was neutralized with acetic acid in a stoichiometric ratio to obtain a solid powder, which was dried and calcined to obtain a sample recorded as embryo powder 1#.

[0095] Using methyl orthosilicate as silicon source, tetrabutyl titanate as titanium source, trimethylamine as alkali source and anhydrous ethanol as protective agent, a mixed solution II of SiO2: 0.033TiO2: 0.05C3H9N: 0.3S: 16H2O is obtained according to the steps. At this time, embryo solution I is added to the mixed solution II, wherein the SiO2 content in the embryo solution I accounts for 10% of the SiO2 content in the mixed solution II to form a final mixed solution. The mixed solution is placed in a synthesis reactor with a polytetrafluoroethylene liner and crystallized at 170°C for 4 hours to obtain a titanium silicon molecular sieve. The product is centrifuged, washed, dried and calcined to obtain the final molecular sieve product. XRF results show that the product has Si / Ti = 36.7, recorded as sample 1#.

[0096] Example 2 Preparation of samples 2# to 19#

[0097] Sample 2 # ~19 # The raw material types, raw material ratios, and crystallization conditions are shown in Table 1. The batching process is the same as that of Sample 1 in Example 1. # Preparation.

[0098] Table 1. Ingredients and crystallization conditions for molecular sieve synthesis in Examples 1 to 19

[0099]

[0100]

[0101] Example 20 Sample 1 # ~19 # XRD and IR analysis of synthetic embryo solution including solid

[0102] The XRD results of the embryo powders prepared in the embodiment are all amorphous, but the infrared IR characterization contains a large number of characteristic peaks attributable to the 5-membered ring structure that are consistent with the positions of MFI zeolite, such as Figure 1From the XRD spectrum of embryo powder 1#, it can be seen that the embryo powder is amorphous. The XRD spectrum results of embryo powders 2#-19# are similar to Figure 1 Close, indicating that they are all amorphous structures; Figure 2 This is the IR spectrum of embryo powder 1#. It can be seen that at 550cm -1 There are characteristic peaks attributable to the 5-membered ring structure nearby. The IR spectra of embryo powder 2#-19# are similar to Figure 2 Close, at 550cm -1 Vibration peaks consistent with MFI structure zeolite can be observed nearby, indicating that the synthesized embryo contains a large number of zeolite structural units.

[0103] Embodiment 21

[0104] Sample 1 # ~19 # XRD, SEM, UV-Vis, N2 physical adsorption and pore size distribution analysis

[0105] X-ray diffraction, scanning electron microscopy and ultraviolet diffuse reflectance were used to characterize sample 1. # ~19 # Conduct analysis.

[0106] Sample 1 prepared in Example # ~19 # All of them are TS-1 molecular sieves with high purity and high crystallinity and MFI topology, such as Figure 3 Medium sample 1 # XRD spectrum of sample 2 # ~19 # The XRD results show that the position and shape of the diffraction peaks are basically the same, and the relative peak intensity fluctuates within the range of ±5% depending on the synthesis conditions. # ~19 # It has the characteristics of MFI structure and has no impurity crystals; Sample 1 # ~19 # All of them have nano-flake morphology, typical examples are Figure 4 From the SEM image of sample 1#, we can see that the product has a flake structure with a size of about 200nm*150nm*50nm, of which the size of the 10-membered ring b-axis direction is only about 50nm, and the particle size is relatively uniform. Sample 2 # ~19 # The SEM images show that the product morphology and particle size are Figure 1 Sample 1# is close in size; Sample 1 # ~19 # The Ti species in the system all exist as tetracoordinated framework Ti species, typical representatives of which are Figure 5From the UV-Vis graph of sample 1#, it can be seen that the Ti in the product is mainly in the form of tetracoordinate (210-220nm), and there is almost no non-framework Ti (230-270nm) and nano-TiO2 (310-330nm); sample 2 # ~19 # The UV-Vis graph of is similar to that of sample 1#, mainly existing in the form of tetracoordinate species, without any non-framework Ti and TiO2 species. Figure 6 and Figure 7 The physical adsorption curve and pore size distribution diagram of the product are shown respectively. It can be seen that under the premise of ensuring the micropore volume of the product, the mesopore volume of the product reaches 0.32cm 3 g -1 , the mesopore size distribution is between 10-30nm; Sample 2 # ~19 # The physical adsorption curve and pore size distribution of Figure 6 and Figure 7 Similarly, it can be seen that the product obtained by this solution has both high skeleton Ti content and multi-level pore structure, and the product yield can reach 92%.

[0107] Comparative Example 1 Comparative Sample 1 # Preparation

[0108] The specific proportion of ingredients, the preparation process and the crystallization conditions are the same as those of Sample 1 in Example 1. # The preparation method is as follows, except that the crystallization time of the embryo solution I is extended to 48 hours, the embryo solution is neutralized with acetic acid in a stoichiometric ratio to obtain a solid powder, the powder is dried and calcined, and the obtained sample is recorded as embryo powder comparative sample 1#. The final sample synthesized using the embryo solution synthesized in comparative example 1 is recorded as comparative sample 1#.

[0109] UV-Vis analysis of Example 23 Comparative Example 1#

[0110] The XRD, SEM and physical adsorption results (not shown) of sample 1# are similar to those of sample 1#; however, its UV-Vis Fig. 9 As shown in the figure, in addition to the framework Ti, the comparative sample 1# also contains a large amount of non-framework Ti species (230-270cm -1 ). It can be seen from this that the pre-crystallized seed solution is not conducive to the entry of Ti species into the framework during induced synthesis. Therefore, it is critical to strictly control the aging conditions of the embryo solution to avoid excessive crystallization.

[0111] The main reason for producing an amorphous embryo in the present invention is to control the aging time and the aging temperature.

[0112] Compared with the seed crystal, the embryo solution of the present invention has a significantly smaller grain size of the final product, and the Ti species are all 4-coordinated and do not contain non-framework Ti and the like.

[0113] If the embryo solution of the present invention is over-crystallized to form a partially crystalline product, although the morphology of the final product is not much different, the Ti coordination is significantly different. If conventional seed crystals are used, not only is the Ti coordination poor, but the particle size is also significantly increased.

[0114] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for synthesizing titanium silicon molecular sieve TS-1, characterized in that: The method comprises the following steps: S1: mixing raw materials containing a silicon source, a quaternary ammonium base template and water to obtain an initial gel mixture A, and heating and crystallizing the initial gel mixture A under a closed condition to obtain a crystal blank solution I; the solid in the crystal blank solution I has an amorphous structure; S2: Mixing raw materials containing silicon source, alkali source R, water, titanium source and protective agent S to obtain gel mixture II; S3: The crystal blank solution I in step S1 and the gel mixture II in step S2 are mixed to obtain a gel mixture III. The gel mixture III is heated and crystallized under closed conditions to obtain the titanium silicon molecular sieve TS-1.

2. The method for synthesizing titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: In step S1, the solid particles in the crystal blank solution I have a size of 10 to 20 nm, and the particle structure contains a five-membered ring structure.

3. The method for synthesizing titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: In step S1, the molar ratio of the silicon source, the quaternary ammonium base template and the water in the initial gel mixture A is: Template: SiO2 = 0.10-0.50:1; H2O:SiO2=4~20:1; The molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the template is calculated as the molar number of the quaternary ammonium base, and the molar number of the water is calculated as the molar number of H2O; Preferably, in step S2, the molar ratio of the silicon source, the titanium source, the alkali source R, the protective agent S and the water in the gel mixture II is: SiO2: TiO2: R: S: H2O=1: (0.02~0.10): (0.01~0.20): (0.04~ 0.2):(6~30); Among them, the molar number of the silicon source is calculated as the molar number of SiO2, the molar number of the titanium source is calculated as the molar number of TiO2, the molar number of R is calculated as the molar number of the alkali source R, the S is calculated as the molar number of the protective agent S, and the water is calculated as the molar number of H2O.

4. The method for synthesizing titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: The structural formula of the quaternary ammonium base template is Formula I: Among them, R in Formula I 1 , R 2 , R 3 , R 4 Each independently selected from any one of C1 to C4 alkyl groups, R 1 , R 2 , R 3 and R 4 Same or different; Preferably, the quaternary ammonium base template is selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide.

5. The method for synthesizing titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: The gel mixture II in step S2 is obtained by mixing the initial gel mixture B and the initial gel mixture C; The initial gel mixture B is obtained by mixing a silicon source, an alkali source R and water; the molar ratio of each component in the initial gel mixture B is: R: SiO2 = 0-0.10:1; H2O:SiO2=6-30:1; The initial gel mixture C is obtained by mixing a titanium source and a protective agent S; the molar ratio of each component in the initial gel mixture C is: S: TiO2 = 4-20:1; Wherein, the mole number of the silicon source is calculated as the mole number of SiO2, the mole number of the titanium source is calculated as the mole number of TiO2, the mole number of the alkali source R is calculated as the mole number of R, the mole number of the protective agent S is calculated as the mole number of S, and the mole number of the water is calculated as the mole number of H2O; Preferably, in step S3, the molar content of SiO2 in the crystal blank solution I is 3-10% of the molar content of SiO2 in the gel mixture II.

6. The method for synthesizing titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: In step S1, the temperature of the crystallization I is 60 to 140° C., and the time of the crystallization I is 0.5 to 24 hours; Preferably, in step S3, the temperature of the crystallization II is 140-220° C., and the time of the crystallization II is 0.5-48 h.

7. The method for synthesizing titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: The silicon source in the initial gel mixture A is selected from at least one of silica sol, methyl orthosilicate and ethyl orthosilicate; Preferably, the silicon source in the gel mixture II is selected from at least one of silica sol, silica gel, chromatography column silica gel, methyl orthosilicate, ethyl orthosilicate and white carbon black; The titanium source is selected from at least one of tetraethyl titanate, tetrabutyl titanate, titanium tetrachloride, titanium sulfate and titanium isopropoxide; The protective agent S is selected from at least one of ethanol, isopropanol, acetylacetone, acetic acid and triethanolamine.

8. The method for synthesizing titanium silicon molecular sieve TS-1 according to claim 1, characterized in that: The alkaline source R in the gel mixture II is selected from a compound having a structure of formula II: Wherein, R1, R2, and R3 in Formula II are independently selected from H or an alkyl group having 1 to 4 carbon atoms; Preferably, the alkaline source R in the gel mixture II is selected from at least one of aqueous ammonia, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine and tri-n-butylamine; Preferably, in step S3, the titanium silicon molecular sieve TS-1 is calcined in air at a temperature of 400 to 600°C.

9. A titanium silicon molecular sieve TS-1, characterized in that: The titanium silicon molecular sieve is synthesized by the synthesis method of titanium silicon molecular sieve TS-1 described in any one of claims 1 to 8.

10. The titanium silicalite molecular sieve TS-1 according to claim 9, characterized in that: The titanium silicon molecular sieve TS-1 has a multi-level pore structure of micropores and mesopores; Preferably, the titanium silicon molecular sieve TS-1 has an MFI topological structure, wherein the Ti species has a four-coordinate structure; the pore size of the mesopore is 5nm to 50nm, and the volume of the mesopore is 0.25 to 0.43cm 3 g -1 The titanium silicalite molecular sieve TS-1 has a nano-flake morphology, and its length, width and thickness are 200-300nm, 150-250nm and 40-60nm respectively.

Citation Information

Patent Citations

  • Method for preparing multi-level porous channel beta zeolite

    CN101538049A

  • Hierarchical pore Y-type molecular sieve, preparation method and application thereof

    CN112661166A